Effects of Ascorbic Acid, Alpha-Tocopherol and Allopurinol on Ischemia-Reperfusion Injury in Rabbit Skeletal Muscle: An Experimental Study - Bilgehan Erkut; Ahmet özyazicioğlu; Bekir Sami Karapolat; Cevdet Uğur Koçoğullari; Sait Keles; Azman Ateç; Cemal Gundogdu; Hikmet Kocak (AboutScience Srl, 2007)
Purpose Ischemia reperfusion injury to skeletal muscle, following an acute arterial occlusion is important cause of morbidity and mortality. The aim of the present study was to determine and evaluate the effects of ascorbic acide, alpha-tocopherol and allopurinol on ischemia reperfusion injury in rabbit skeletal muscle. Methods Forty-eight New Zealand white rabbits, all male, weighing between 2.5 to 3.0 (mean 2.8) kg, were used in the study. They were separated into four groups. Group I was the control group without any drugs. The other groups were treatment groups (groups II, III, and IV). Group II rabbits administrated 50 mg/kg ascorbic acide and 100 mg/kg alpha-tocopherol 3 days prior to ischemia, group III rabbits received 50 mg/kg allopurinol 2 days prior to ischemia, and group IV rabbits were administrated both 50 mg/kg ascorbic acide, 100 mg/kg alpha-tocopherol 3 days prior to ischemia and 50 mg/kg allopurinol 2 days prior to ischemia. Two hours ischemia and 2 hours reperfusion were underwent to the treatment groups. At the end of the reperfusion periods, muscle samples were taken from rectus femoris muscle for determination of superoxide dismutase, catalase and glutathione peroxidase activities as antioxidant enzymes, and malondialdehyde as an indicator of lipid peroxidation and xanthine oxidase levels as source hydroxyl radical. Besides, histopathological changes (edema, inflammation, ring formation and splitting formation) were evaluated in the muscle specimens. Results In the treatment groups; superoxide dismutase (U/mgprotein), catalase (U/mgprotein), and glutathione peroxidase (U/mgprotein) levels increased, malondialdehyde (nmol/mgprotein) and xanthine oksidase (mU/mgprotein) levels decreased compared to control I ( p < 0.05). Increase of superoxide dismutase, catalase, and glutathione peroxidase levels were the highest and decrease of malondialdehyde and xanthine oxidase levels were the highest in group IV compared to groups II and III, but no significant as statistically. Also amount of cellular injury in group II, III, and IV were lower than group I. Conclusions Antioxidant medication may help lowering ischemia reperfusion injury. In our study, all drug medications are shown to be able to have an effective role for preventing ischemia reperfusion injury. Moreover, ascorbic acide + alpha-tocopherol + allopurinol group (group IV) may have a beneficial effect to decrease the local and systemic damage due to ischemia-reperfusion injury.